2023
DOI: 10.1021/acsnano.2c09918
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Single Atom Confinement Effects on Catalysis in 1T-Phase Molybdenum Disulfide

Abstract: Active sites are atomic sites within catalysts that drive reactions and are essential for catalysis. Spatially confining guest metals within active site microenvironments has been predicted to improve catalytic activity by altering the electronic states of active sites. Using the hydrogen evolution reaction (HER) as a model reaction, we show that intercalating zinc single atoms between layers of 1T-MoS2 (Zn SAs/1T-MoS2) enhances HER performance by decreasing the overpotential, charge transfer resistance, and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…131 Numerous studies have reported the potential of metallic 1T phase MoS 2 for enhancing the HER performance. [132][133][134] The electrochemical potential-cycling route was utilized to synthesize a Pt-doped MoS 2 catalyst (Pt@MoS 2 ). This method involved simultaneously inducing a transition from the 2H semiconducting phase to the 1T metallic phase and doping Pt into the basal plane of MoS 2 (Fig.…”
Section: Metal Phosphide Based Supportsmentioning
confidence: 99%
“…131 Numerous studies have reported the potential of metallic 1T phase MoS 2 for enhancing the HER performance. [132][133][134] The electrochemical potential-cycling route was utilized to synthesize a Pt-doped MoS 2 catalyst (Pt@MoS 2 ). This method involved simultaneously inducing a transition from the 2H semiconducting phase to the 1T metallic phase and doping Pt into the basal plane of MoS 2 (Fig.…”
Section: Metal Phosphide Based Supportsmentioning
confidence: 99%
“…[16][17][18][19] Among them, Electrocatalytic HER is considered to be a clean, efficient and sustainable alternative strategy for hydrogen production from fossil fuels. [20][21][22] The process of hydrogen production from electrolytic water, like other chemical reactions, requires overcoming the energy barriers from reactants to activation products for the reaction to proceed smoothly. [23][24][25] Development of high performance HER electrocatalysts has become an important strategy for hydrogen production.…”
Section: Introductionmentioning
confidence: 99%
“…For example, conductive additives or scaffolds are used to construct continuous electron pathways. Strong adsorbents and/or porous structures are developed to capture or confine polysulfides inside cathodes. , A strong adsorbent also influences the deposition models of Li 2 S. , In addition, catalysts are studied to accelerate the conversion of polysulfides and suppress the shuttling effects. , Among various previously reported catalysts, transition metal chalcogenides and pnictogenides receive intense interests. Chen and co-workers designed Co 3 O 4 nanopolyhedra with different dominant lattice planes to optimize the polysulfide adsorption and enhance catalytic conversion owing to varied oxidation states and coordination environments of the catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…However, these 2D disulfides usually expose less active basal planes because of strong covalent in-plane bonding and weak van der Waals interactions between layers. Previous efforts , had been devoted to tuning the crystal growth habit to expose edge sites because edges are more active than basal sites. In addition, dopants or vacancies were also engineered to increase the activity of basal planes. Despite the success of improving the catalytic activity, dopants and vacancies may have potential thermodynamic instability and probably decrease the long-term cyclability.…”
Section: Introductionmentioning
confidence: 99%